Fragments of Targum Onkelos of Exodus Recently Found in Rijeka, Croatia - Tepert, Darko (Liber Annuus, 2011)
Abstract During the research in the library of the Monastery of the Capuchin Franciscan Friars in Rijeka, Croatia, two folia of a parchment were found in the cover of a 15th century book. The parchments contain an interlinear Hebrew-Aramaic fragment of a manuscript from the Book of Exodus (Exodus 21:23-22:8a; 26:26b- 27:10). In relation to the calligraphic models of Hebrew and Aramaic texts, the origin of the manuscript may be dated between the 12th and 15th centuries, and it may be said to belong to the Ashkenazi Bible-copying tradition, while an examination of the parchment treatment and its preparation for writing places it into the late 13th or early 14th century. The Hebrew text, which is vocalised, does not seem to vary much from the accepted vocalised Hebrew text, except for a certain number of orthographic differences. The Hebrew text of The Book of Exodus is accompanied by a corresponding masora parva which mostly corresponds with what is common in other manuscripts, while masora magna is not legible enough to reach a final conclusion. The Aramaic text contains a vocalised Targum Onkelos, but with certain differences not only in orthography but also in the content. The number and types of differences in relation with the usual text of Targum Onkelos indicate that FgCap VlaTep differs from it in three ways: (i) it attempts to further harmonise the text with the Hebrew Bible, (ii) it avoids matres lectionis and (iii) it contains quite a few grammatical structures characteristic of Palestinian Aramaic. The manuscript was undoubtedly not used in synagogal liturgy, but was an aid in the personal (scholarly) study of the Holy Scripture, and the fragments were a part of a larger codex that could have contained either The Book of Exodus or the complete Torah.